Bookreview: Finland in the margins of the Viking world - Willson Kendra (Suomen Kansantietouden Tutkijain Seura ry., 2025)
Joonas Ahola and Frog with Clive Tolley (eds.) 2014. Fibula, fabula, fact. The Viking Age in Finland. Helsinki: Finnish Literature Society. 519 pp.
Joonas Ahola, Frog, and Jenni Lucenius (eds.) 2014. The Viking Age in åland. Insights into identity and remnants of culture. Sastamala: Finnish Academy of Arts and Letters. 427 pp.